Assessment of aerosol optical properties using remote sensing over highly urbanised twin cities of Pakistan. (August 2018) - Awais, Muhammad; Shahzad, Muhammad I.; Nazeer, Majid; Mahmood, Irfan; Mehmood, Shahid; Iqbal, Muhammad Farooq; Yasmin, Nighat; Shahid, Imran
Abstract: Ability of aerosols to attenuate solar radiation can be measured in terms of Aerosol Optical Depth (AOD) or Aerosol Optical Thickness (AOT), which can be accurately monitored from ground-based stations using ambient air samplers. However, such methods are very expensive and spatially incomplete whereas, satellite-based remote sensing of AOD can be used effectively to quantify the effects of atmospheric aerosols. Developing countries like Pakistan need to enhance usage of such techniques (i.e. ambient air samplers). Currently, Lahore and Karachi are the only two cities in Pakistan where ground-based stations i.e. Aerosol Robotic Network (AERONET) are available for air quality measurements. Therefore, this is the first ever study to monitor AOD of Pakistan for cities other than Lahore and Karachi. This study uses AOD simultaneously from Moderate Resolution Imaging Spectroradiometer (MODIS) and a handheld sun photometer in densely populated twin (adjoining) cities of Rawalpindi and Islamabad. It is found that MODIS (Terra and Aqua) can reveal the distribution of aerosols over these cities with 80% of agreement to handheld sun photometer. Mean AOD calculated from green (508 nm) and red (625 nm) channels of handheld sun photometer is 0.49 and 0.37 respectively, with MODIS retrieved AOD found to be 0.40 in green channel. A standard deviation of 0.29 was observed in MODIS 0.26 in green and 0.20 in red channel of the sun photometer in monthly average measurements. There was good agreement between AOD from MODIS and handheld sun photometer with a Slope of 0.87, MAE of 0.15 and RMSE of 0.19 for green channel. However, there was a slightly more than unity slope of 1.14, MAE of 0.12, RMSE of 0.17 for red channel. The area is abundant in medium sized aerosols. Results of the study will be helpful in establishing a baseline for the accuracy assessment of AOD retrieved from satellite over Rawalpindi/Islamabad. Further, it will also help policy makers to measure the impacts of spatiotemporal variations of size and nature of aerosols on air quality and health of the region. Highlights: First ever study of AOD using handheld sun photometer in twin cities of Pakistan. Seasonal analyses suggest a direct relationship between temperature and AOD. GLOBE handheld sun photometer is a reliable device for the retrieval of AOD.